Outcomes of patients treated with blood transfusion in a contemporary tertiary intensive cardiac care unit. (3rd October 2022) - Karameh, H; Taha, L; Karmi, M; Hamayel, K; Perel, N; Steinmetz, Y; Levi, N; Shaheen, F; Manassra, M; Maller, T; Glikson, M; Asher, E
Abstract: Background: Different trials showed that patients treated with blood transfusion (BT) have unfavorable prognosis regarding outcomes and mortality. Nevertheless, outcomes in patients treated with BT hospitalized in a contemporary tertiary intensive cardiac care unit (ICCU) is limited. Objective: To determine mortality rate in patients treated with BT in a contemporary tertiary ICCU. Methods: A prospective single center study to evaluate short- and long-term mortality rate of patients treated with BT between January 2020 and December 2021 in a tertiary ICCU. Outcomes: During the study period 2132 consecutive patients were admitted with a mean age of 66.9±16 and 650 (30.5%) of them were women. Of the total population, 108 (5%) patients were treated with BT (BT-group) during their hospitalization. Patients were followed-up for 2 years with a median [IQR] follow up time of 82.5 [12.25–240.50] days in BT-group vs. 138.5 [34–325, 75] days in the non-BT (NBT) group. Mean age was 73.81±14 years in BT-group vs. 66.59±16 years in NBT-group, p<0.0001. There was a higher rate of female gender in the BT-group 48.1% vs. 29.5% in the NBT, p<0.0001. Crude mortality rate was 29.6% in BT-group and 9.2% in NBT-group, p<0.0001. Median [IQR] length of stay was 5 [2–6] days in BT-group vs. 3 [2–4] days in the NBT-group. Multivariate Cox analysis for (Female gender, prior trans-catheter aortic valve replacement, prior cardiac intervention, sepsis, history of congestive heart failure, pulmonary hypertension, pacemaker implantation and anemia) showed that BT was independently associated with more than two folds the mortality rate [HR=2.19 95% CI (1.47–3.62)] as compared with the NBT-group, p<0.0001. Receiver operating characteristic curve (ROC) was plotted for multivariable analysis and showed area under curve (AUC) of 0.8, 95% CI [0.760–0.852]. Conclusion: Even in contemporary tertiary ICCU, with advanced technology, equipment and delivery of care, BT remains a strong predictor for short- and long-term mortality. Funding Acknowledgement: Type of funding sources: None.